Challenging the Status Quo to Shape Food Systems Transformation from a Nutritional and Food Security Perspective Second Edition - Raposo, António; Zandonadi, Renata Puppin; Botelho, Raquel Braz Assunção (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The present reprint aimed to present original research articles and reviews concerning the following:Access: affordability, allocation, and preference of food;Availability: the production, distribution, and exchange of food;Circularity in food systems at local, regional, or global levels;The development, impact, and ethics of novel and data-driven technologies in food systems;Food security and policy, governance, institutions, and trade;Influencing food consumption and demand regarding the food environment;The stability and dynamics of food security aspects;Sustainable food systems and agro-ecological food production;Utilization: the nutritional value, social value, and safety of food.